2015
DOI: 10.1590/1516-4446-2014-1533
|View full text |Cite
|
Sign up to set email alerts
|

Motor development of children with attention deficit hyperactivity disorder

Abstract: Objective: To compare both global and specific domains of motor development of children with attention deficit hyperactivity disorder (ADHD) with that of typically developing children. Methods: Two hundred children (50 children with clinical diagnoses of ADHD, according to the DSM-IV-TR and 150 typically developing controls), aged 5 to 10 years, participated in this crosssectional study. The Motor Development Scale was used to assess fine and global motricity, balance, body schema, and spatial and temporal org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Earlier investigators reported delay in motor development of ADHD probands [37]. Our study group showed delayed motor development in 26% probands.…”
Section: Discussionsupporting
confidence: 62%
“…Earlier investigators reported delay in motor development of ADHD probands [37]. Our study group showed delayed motor development in 26% probands.…”
Section: Discussionsupporting
confidence: 62%
“…Neuropsychological studies of childhood ADHD have suggested deficits on measures of perceptual reasoning and language (Woo & Rey, 2005). Motor abilities have been implicated in both childhood and adult ADHD research (Rosa Neto, Goulardins, Rigoli, Piek, & Oliveira, 2015; Stray et al, 2013). Future research should examine these domains more comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Several motor difficulties have been identified, including problems with gross motor skills (i.e., ball skills; Piek, Pitcher, & Hay, 1999), fine motor skills in manual dexterity and bimanual coordination tasks (Piek et al., 1999; Rommelse et al., 2007), balance (Mao et al., 2014), gait, and postural control (Buderath et al., 2009; Papadopoulos et al., 2014). In addition, children with ADHD have shown poor performance on tests with motor development scales when compared with typically developing children (Goulardins et al., 2013; Poeta & Rosa-Neto, 2007; Rosa Neto et al., 2015; Vidarte, Ezquerro, & Giraldez, 2009).…”
Section: Methods Of Reviewmentioning
confidence: 99%